Late-Onset Sepsis in Very Low Birth Weight Infants from Singleton and Multiple Gestation Births - Boghossian, Nansi S. (2013)
OBJECTIVES: To describe and compare incidence of late-onset sepsis (LOS) and demographic and clinical characteristics associated with LOS in very low birth weight (VLBW) infants from singleton and multiple births and to examine the heritability in susceptibility to LOS among VLBW twins by comparing same-sex with unlike-sex twin pairs. STUDY DESIGN: We studied infants with birth weight 401–1500 grams cared for at clinical centers of the NICHD Neonatal Research Network 2002–2008. Only the first episode of LOS was examined. Stepwise logistic regression models were fitted separately for singleton and multiple pregnancies to examine the maternal and neonatal factors associated with LOS. LOS due to only gram-negative bacteria among singleton and multiple pregnancies was also examined in separate models. The heritability of LOS was estimated by examining concordance of LOS between twins from same-sex and unlike-sex pairs. RESULTS: LOS occurred in 25.0% (3797/15,178) of singleton and 22.6% (1196/5294) of multiple VLBW infants. Coagulase-negative staphylococci were the most common infecting organisms, accounting for 53.2% of all LOS episodes in singletons and 49.2% in multiples. E. coli and Klebsiella species were the most commonly isolated gram-negative organisms, and Candida albicans was the most commonly isolated fungus. Concordance of LOS was not significantly different between same-sex and unlike-sex twin pairs. CONCLUSIONS: LOS remains a common problem in VLBW infants. The incidence of LOS is similar for singleton and multiple infants. Similar concordance of LOS in same-sex and unlike-sex twin pairs provided no evidence that susceptibility to LOS among VLBW infants is genetically determined.